A novel spectrophotometric method for the determination of copper ion by using a salophen ligand, N, N′-disalicylidene-2, 3-diaminopyridine. Issue 5 (1st September 2017) - Babayeva, Könül; Demir, Serkan; Andac, Müberra
Abstract: In this study, a novel, selective and highly sensitive spectrophotometric method has been developed for the determination of copper(II) by using a new chromogenic reagent N, N′-bissalicylidene-2, 3-diaminopyridine (H2 IF). The absorbance was measured at λmax = 414 nm. Experimental conditions were optimized, and Beer's law was observed in the concentration range of 6.35–318 μg L −1 of copper. The molar absorptivity of the complex was calculated and found to be 1.46 × 10 5  L mol −1  cm −1 . The detection and quantification limits were calculated and found to be 6.38 μg L −1 and 21.27 μg L −1, respectively. The calculated relative standard deviation (n = 5) was 0.62% for a standard solution including 63.5 μg L −1 copper(II). The interference effects of the common ions have been studied and the statistical assessment of the obtained results is presented. The developed method was applied for the determination of copper in water samples. The reliability and accuracy of the developed method was proven by the analysis of a waste water standard.